EFFECT OF SITUATIONAL LEADERSHIP STYLE, COMPENSATION AND MOTIVATION ON EMPLOYEE PERFORMANCE IN PT. BANK RAKYAT INDONESIA (PERSERO), Tbk. KEDIRI BRANCH - Selviasari, Rike (JEMIS (Journal of Engineering & Management in Industrial System), 2019)
This research was conducted at PT. Bank Rakyat Indonesia (Persero) KCP Ringinrejo Tbk. Branch Kediri This study uses Styles Situational Leadership and Compensation Committee as an independent variable, motivation as an intervening variable and performance as the dependent variable.The purpose of this study to analyze and determine the influence of leadership style and Compensation for performance through motivation as an intervening variable. The samples used were employees of PT. Bank Rakyat Indonesia (Persero), Tbk. Branch Kediri with a total sample of 52 respondents using simple random sampling method. The analysis includes the validity, reliability, classic assumption test, test models, linear regression analysis and intervening.Based on the above results it can be seen that the Situational Leadership Styles and Compensation positive and significant impact on motivation, Situational Leadership Style and Compensation positive and significant impact on performance.Based on the two above analysis can be tested mediating (intervening) so that it is known that the variables of motivation to become an intervening variable because the calculation of standardized coefficients for the indirect effect of leadership style Situational and Compensation for Performance through work motivation is greater than the direct influence Styles Situational Leadership and Compensation on performance